Performance of sunflower cultivars in the western region of Santa Catarina State - Simioni, Juliano (2020)
The sunflower (Helianthus annuus L.) has been shown as an option to be cultivated in many regions of Brazil. This study aims to evaluate the performance of sunflower genotypes during the harvest period of 2007/08, in the western region of Santa Catarina State. The experiment design was randomized blocks with four repetitions for each treatment.Twenty-six genotypes were evaluated concerning these traits: cycle until bloom, plant density, plant height, diameter of the capitulum, number of plants fallen down, number of broken plants, curve of the stem, and yield. The cultivars differed significantly in relation to the traits studied, except for the density and the number of fallen down plants. Theaverage yield was 3,070kg/ha, above the national average yield (1,475kg/ha). Thus, it is possible to conclude that there are cultivars with potential to be cultivated in the western region of Santa Catarina.